Human pyramidal to interneuron synapses are mediated by multi-vesicular release and multiple docked vesicles - Gábor Molnár; Márton Rózsa; Judith Baka; Noémi Holderith; Pál Barzó; Zoltan Nusser; Gábor Tamás (eLife, 2016)
Classic theories link cognitive abilities to synaptic properties and human-specific biophysical features of synapses might contribute to the unparalleled performance of the human cerebral cortex. Paired recordings and multiple probability fluctuation analysis revealed similar quantal sizes, but 4-times more functional release sites in human pyramidal cell to fast-spiking interneuron connections compared to rats. These connections were mediated on average by three synaptic contacts in both species. Each presynaptic active zone (AZ) contains 6.2 release sites in human, but only 1.6 in rats. Electron microscopy (EM) and EM tomography showed that an AZ harbors 4 docked vesicles in human, but only a single one in rats. Consequently, a Katz’s functional release site occupies ~0.012 μm2 in the human presynaptic AZ and ~0.025 μm2 in the rat. Our results reveal a robust difference in the biophysical properties of a well-defined synaptic connection of the cortical microcircuit of human and rodents.